Kelestarian Gamelan dalam Komposisi Piano Etude No. 5 Karya Razak Abdul Aziz: The Sustainability of Gamelan through Razak Abdul Aziz’s Etude No. 5 for Piano Solo - Mohd Fairuz Zamani; Nur Fardilla Nadia Abu Bakar (Wacana Seni Journal of Arts Discourse, 2025)
Sustainability is a global focus nowadays, especially when the United Nations (UN) introduced the Sustainable Development Goals (SDGs) in 2015. Music can be mapped to all 17 SDGs. Among the musical arts recognised by the UNESCO is gamelan music. Although gamelan gained international recognition, its sustainability is threatened by the current of modernisation, like other traditional music. Composer Razak Abdul Aziz had anticipated this threat in advance and incorporated gamelan elements into his piano composition Etude No. 5. Western composers such as Claude Debussy, Erik Satie, Leopold Godowsky, and Lou Harrison have adapted gamelan elements into their respective compositions, alongside local composer Marzelan Salleh who uses gamelan elements and scale associations for narration in his work Puteri Gunung Ledang. The works of these composers prove that gamelan elements can be preserved through adapting them into piano compositions. The study conducted on Etude No. 5 uses interviews with the composer, score analysis, and related reading materials as its main research tools. The results found that the composer has adapted the colotomic structure of gamelan into this work using several formulas, namely (1) a modified multiple of eight, (2) a standard multiple of eight, and (3) a modified multiple of six by using certain note values in determining the number of notes in any given colotomic structure. The composer also used micro- and macro-colotomic structures in this composition. Creative approach through the composer’s individual aesthetics based on ideas derived from the Chaos Theory were also used in the adaptation process. Traditional art needs to be preserved through adaptation into contemporary works to stay relevant in the era of development and modernisation and to attract the interest of the audience, especially the young and foreigners, to learn and understand the art of Malaysian cultural heritage, thus placing Malaysia on the global pedestal.